2011
DOI: 10.1128/jcm.05341-11
|View full text |Cite
|
Sign up to set email alerts
|

Differing Neisseria gonorrhoeae Bacterial Loads in the Pharynx and Rectum in Men Who Have Sex with Men: Implications for Gonococcal Detection, Transmission, and Control

Abstract: The bacterial loads for gonococcal infections of the pharynx and rectum were determined among men with male sexual partners. The median bacterial load for rectal infections (18,960 copies/swab) was significantly higher than the load for pharyngeal infections (2,100 copies/swab; P ‫؍‬ 0.001). Bacterial loads among men with symptomatic proctitis were strikingly high (median, 278,000 copies/swab).Gonorrhea is one of the most common sexually transmitted diseases, and study results suggest that rectal gonorrhea enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 8 publications
7
80
2
Order By: Relevance
“…In 2013, Bissessor et al reported that the gonococcal bacterial DNA load in the pharynx is about 2,100 copies/swab (14), which is almost 80-fold lower than the estimate in our study (1.7 ϫ 10 5 copies/swab). It is possible that the sampling technique may explain the lower levels found in the Bissessor study compared to our study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In 2013, Bissessor et al reported that the gonococcal bacterial DNA load in the pharynx is about 2,100 copies/swab (14), which is almost 80-fold lower than the estimate in our study (1.7 ϫ 10 5 copies/swab). It is possible that the sampling technique may explain the lower levels found in the Bissessor study compared to our study.…”
Section: Discussioncontrasting
confidence: 55%
“…N. gonorrhoeae contains 11 copies of opa genes and a single copy of the porA gene. The N. gonorrhoeae load was calculated by comparing quantitative PCR (qPCR) crossing points to the standard curve constructed by the amplification of different copy numbers from an opa assay (14).…”
Section: Methodsmentioning
confidence: 99%
“…The subanalysis of PS testing according to anatomical site of infection showed that PS testing performed less well in detecting pharyngeal C. trachomatis (sensitivity, 69% [95% CI, 39 to 91%]) and N. gonorrhoeae (sensitivity, 89% [95% CI, 83 to 94%]). All of the samples for the PS were self-taken swabs, and this lower performance of PS testing in detecting pharyngeal infec- tions may be due to sampling error or the lower organism loads seen in pharyngeal infections (22). There is evidence that the swabbing technique is important for optimal isolation of pharyngeal gonorrhea (23), and inadequate self-sampling could account for the lower detection rates for PS testing.…”
Section: Discussionmentioning
confidence: 99%
“…NAATs have been shown to be significantly more sensitive than culture in the detection of chlamydia and gonorrhoea, particularly in extra-genital sites (103)(104)(105)(106)(107)(108). Owing to cross-reactivity with nongonorrhoea Neisseria species, all NAAT tests for gonorrhoea from all sites should be confirmed with supplementary tests to improve specificity (109)(110)(111).…”
Section: Chlamydia and Gonorrhoeamentioning
confidence: 99%